POLITIK MASYARAKAT, NEGARA, DAN KESENIAN - Aprinus Salam (Badan Pengembangan dan Pembinaan Bahasa, 2014)
This paper explores how post-New Order Indonesia has seen a declined emphasis on government legitimization and an increased emphasis on the power of the populace. In this situation, the populace (society) has the opportunity to perform articulation and politicization from a variety of aspects. Society redefines and reidentifies itself through various negotiations of primordiality, locality, nationality, and globality. Many groups take their own initiative and use their own methods to reach their goals and protect their interests. In creating art, society is generally oriented towards art as business or a politicaleconomic act, such that the role of art in promoting social and national development is considered insignificant. The State is impeded in determining its own capacity, competence, and authority. Society acts